Security study in wimax mesh networks - Muhammad Ashaari Ariff. (2011)
WiMax Mesh mode allows direct communication between Subscriber Stations (SS) without the need of the Base Station (BS), thus improved network coverage. In Multi hop wireless systems such as WiMax Mesh Networks, security emerges as a vital requirement from the threats of both Malicious Sponsor Node (SN) and Candidate Node (CN). Network Entry Process (NEP) is applied for CN to join an active Mesh Network for authentication and registration.